2021
DOI: 10.1101/2021.08.19.456963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CNest: A Novel Copy Number Association Discovery Method Uncovers 862 New Associations from 200,629 Whole Exome Sequence Datasets in the UK Biobank

Abstract: Copy number variation (CNV) has long been known to influence human traits having a rich history of research into common and rare genetic disease and although CNV is accepted as an important class of genomic variation, progress on copy number (CN) phenotype associations from Next Generation Sequencing data (NGS) has been limited, in part, due to the relative difficulty in CNV detection and an enrichment for large numbers of false positives. To date most successful CN genome wide association studies (CN-GWAS) ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 184 publications
(175 reference statements)
0
2
0
Order By: Relevance
“…Finally, we focused on the most frequent CNV in our cohort (frequency = 3.76%; Figure 1 A), the 50 kb 1p36.11 deletion (chr1: 25,599,041–25,648,747), which encompasses RHD (Rhesus [Rh] blood group D antigen [MIM: 111680 ]) and RSRP1 and associated with increased reticulocyte count (β del = 2.7 × 10 9 cells/L; p = 7.8 × 10 −14 ), decreased platelet count (β del = −3.7 × 10 9 cells/L; p = 1.4 × 10 −12 ), and decreased HbA1c (β del = −0.3 mmol/mol; p = 9.3 × 10 −8 ) ( Figure 4 C). Overlap with SNP-GWAS signals for various hematological traits 78 , 79 combined with subsequent replication of the reticulocyte count association based on whole-exome sequencing CNV calls 80 prompted the investigation of the expression of these genes in whole blood. Tissue-specific transcriptomic data from the GTEx project v8 81 ( web resources ) revealed that RHD , a protein whose presence/absence on erythrocyte cell membranes is critical in determining an individual’s Rh blood group, 82 was almost exclusively expressed in whole blood ( Figure 4 D), whereas RSRP1 was ubiquitously expressed, with lower expression in whole blood ( Figure 4 E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we focused on the most frequent CNV in our cohort (frequency = 3.76%; Figure 1 A), the 50 kb 1p36.11 deletion (chr1: 25,599,041–25,648,747), which encompasses RHD (Rhesus [Rh] blood group D antigen [MIM: 111680 ]) and RSRP1 and associated with increased reticulocyte count (β del = 2.7 × 10 9 cells/L; p = 7.8 × 10 −14 ), decreased platelet count (β del = −3.7 × 10 9 cells/L; p = 1.4 × 10 −12 ), and decreased HbA1c (β del = −0.3 mmol/mol; p = 9.3 × 10 −8 ) ( Figure 4 C). Overlap with SNP-GWAS signals for various hematological traits 78 , 79 combined with subsequent replication of the reticulocyte count association based on whole-exome sequencing CNV calls 80 prompted the investigation of the expression of these genes in whole blood. Tissue-specific transcriptomic data from the GTEx project v8 81 ( web resources ) revealed that RHD , a protein whose presence/absence on erythrocyte cell membranes is critical in determining an individual’s Rh blood group, 82 was almost exclusively expressed in whole blood ( Figure 4 D), whereas RSRP1 was ubiquitously expressed, with lower expression in whole blood ( Figure 4 E).…”
Section: Resultsmentioning
confidence: 99%
“…Future release of large sequencing datasets combined to progress in CNV detection tools could resolve these issues and lead to novel discoveries. 21 , 80 , 132 , 133 Second, despite substantial evidence of CNV- and SNP-GWAS signal colocalization, we did not perform robust enrichment analyses, as the non-random genomic distribution and complex nature of CNVs renders simulating the null scenario beyond the scope of this paper. Signal colocalization is likely to be underestimated, as manual literature searches revealed overlaps missed by our annotation pipeline (e.g., 16p13.11 age at menarche signal 101 ) and we obtained a 7% increase in signal colocalization by using GWAS Catalog annotation 6 months apart (31% April 2021 → 38% October 2021).…”
Section: Discussionmentioning
confidence: 99%